Bridging the Gap: Comparing Patient-Clinician Views on Treatment Goals and Communication in the Management of Atopic Dermatitis Within the Asia-Pacific Region - Chia-Yu Chu; Yung Chan; Siriwan Wananukul; Hao Cheng; Nisha Suyien Chandran; Ramesh Bhat; Sang Wook Son; Han-Fang Liao; Sean Gardiner; See-Hwee Yeo; Sophie Bozhi Chen; Qi Qing Ng; et al. (Adis, Springer Healthcare, 2024)
Abstract Introduction It remains unclear how patients with atopic dermatitis (AD) and clinicians perceive the level of patient-clinician communication and if there could be potential lapses. This cross-sectional study aims to compare perspectives between patients with AD and dermatologists regarding communication and treatment expectations in Asia. Methods Moderate-to-severe patients with AD and practicing dermatologists were recruited from eight Asia-Pacific territories, including Mainland China, Hong Kong, India, Japan, Singapore, South Korea, Taiwan, and Thailand. Patients and dermatologists completed separate surveys designed to elicit their expectations regarding AD management, and their perceived level of patient-clinician communication. Patients were also asked about their treatment satisfaction and whether they prefer additional treatment beyond what was prescribed. Demographic information and responses were analyzed using descriptive statistics. The study was reviewed by the institutional review board in each territory, and all participants provided informed consent. Results A total of 1103 patients and 271 dermatologists completed the surveys. Both patients and dermatologists were largely aligned in their top treatment goals in AD management. However, greater proportions of patients prioritized the prevention of exacerbation (78.0% versus 47.2%), minimization of treatment adverse effects (46.4% versus 9.1%), and improvement in mental health (16.0% versus 4.9%), compared with dermatologists. Although patient-clinician communication was observed to be generally good, 10.9% of patients reported dissatisfaction with communication in AD management. The majority of patients were either "very satisfied" or "satisfied" with their latest acute AD treatment, but 65.5% of patients still desired additional treatment. Conclusions This multinational study has provided insights on the perspectives of Asian patients and dermatologists in treatment goals, AD management, and communication. In general, both patients and dermatologists were aligned in treatment goals and there was satisfactory patient-clinician communication in most aspects. However, potential areas of improvement have been identified to further enhance patient-centered care.